2016
DOI: 10.15407/ujpe61.08.0715
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave Beam Refraction in Inhomogeneous Plasma Interferometry

Abstract: The influence of metal impurities on the transport properties of multicomponent thermal plasma at the ambient atmosphere of water vapor has been considered. The calculations are carried out on the basis of the Grad method. It is shown that a small amount of metal impurities can substantially change the magnitude of transport coefficients in comparison with the case of pure water vapor. The influence of the model for the cross-section of electron collisions with a metal atom on the transport properties of therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the case of cylindrical symmetry, Eq. (1) can be rewritten in the form [24] where is the cylinder radius, the current coordinate, ( ) the refractive index, Ψ the angle between the beam propagation direction and the cylinder radius at the point, where the beam falls on the plasma cylinder, and 0 is the beam trajectory turning point, which is determined from the condition…”
Section: Phase Shift At Interferometric Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of cylindrical symmetry, Eq. (1) can be rewritten in the form [24] where is the cylinder radius, the current coordinate, ( ) the refractive index, Ψ the angle between the beam propagation direction and the cylinder radius at the point, where the beam falls on the plasma cylinder, and 0 is the beam trajectory turning point, which is determined from the condition…”
Section: Phase Shift At Interferometric Measurementsmentioning
confidence: 99%
“…In works [23,24], a possibility to use the interferometry with ordinary oblique microwaves for measuring the density in various plasma layers was studied analytically and numerically. It was shown that this method allows the plasma density to be measured in separate layers, if the density profile has a maximum that is shifted from the axis, or if the transverse probing of a plasma formation is impossible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the plasma probing by frequency-modulated waves can be used. This method was applied in works [25,26] to diagnose quasistationary plasma.…”
Section: Specific Features Of Microwave Interferometry With Inclined mentioning
confidence: 99%
“…For experimental determination of plasma rotation velocity, the methods of correlation microwave diagnostics and Doppler reflectometry [4], and also Doppler spectroscopy method [5], are used. When the input angle of a microwave or laser beam into plasma changes, the frequency shifts of a signal passing through various plasma layers are measured and a radial velocity profile is obtained.…”
Section: Introductionmentioning
confidence: 99%